Joining sheets perpendicular to one other by sheet-bulk metal forming. Issue 1 (March 2017) - Bragança, I.; Silva, C.; Alves, L.; Martins, P.
Abstract This paper presents a variant of the traditional 'mortise-and-tenon' joint, which has been used for thousands of years by carpenters and blacksmiths to connect wood or metal parts. The new proposed joint is utilized to fix longitudinally in position two metal sheets (or plates) perpendicular to one other by sheet-bulk metal forming, at room temperature. The development is performed by means of a combined finite element and experimental investigation focused on the identification of the major process parameters and on the understanding of their influence on the overall joining feasibility. Destructive testing is carried out to characterize the performance of the new proposed joint, and an analytical expression is provided to determine the maximum tensile force that the joint can safely withstand.